Kepemimpinan dan Manajerial di Lembaga Pendidikan Islam - Muchlis, Ahmad Nur; Maunah, Binti (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2021)
Education is something that is needed in increasing human resources in a country. One of the institutional organizations having a duty to develop education is an educational institution. An educational institution will be able to advance its institution if it is handled by a professional leader. A leader who becomes the pinnacle of an organization or institution can never be separated from leadership and management. Many people think that leadership and management are the same thing. In fact, have different roles. Therefore, it is necessary to study leadership and management, so that the difference between them is clear. The purpose of this study is to define between leadership and managerial in Islamic educational institutions. The method used in this research is library research. Data and data sources come from the study of books, journals, websites, and other relevant documents and can be used as references in this study. The data analysis in this research is descriptive analysis and content analysis. The result of this research is that leadership is an effort to direct, motivate, guide, and overcome problems in the process of achieving organizational goals together. Management is the process of utilizing the resources owned by the organization to achieve the goals carried out through planning, organizing, directing and controlling. Leaders and managers are different things even though they both play an important role in achieving organizational goals. The leader as a determinant of the vision and mission in the organization, determines the direction and reviews the general picture. Managers carry out the vision and mission, direction, goals and are committed to the organization, then develop plans and agendas as well as appropriate resources to realize the vision and mission of the organization.